BIMBINGAN BAGI ANAK BERKESULITAN BELAJAR SD SWASTA MUHAMMADIYAH 43 KECAMATAN KABANJAHE KABUPATEN KARO - Pelista, Pelista; Jainab, Jainab; Karo, Sringena Br.; Lisnasari, Srie Faizah (Jurnal Pengabdian Mitra Masyarakat, 2024)
This research aims to assist students in developing their potential optimally through comprehensive learning guidance. This research aims to explore and develop an effective guidance program for children with learning difficulties in Elementary School (SD). This activity was carried out at SD Swasta Muhammadiyah 43 Kabanjahe, on May 5, 2024. Learning difficulties experienced by children can affect their academic achievement as well as their emotional and social development. This research uses a qualitative method, namely by conducting orientation to elementary school teachers and parents, providing learning support and mentoring services, as well as monitoring and evaluating program activities. The approach used is an individual technique that applies directive counseling, group guidance applies the home room outside of lesson hours. Data was collected through in-depth interviews with teachers, counselors, and parents, as well as direct observation of students with learning difficulties. The research results show that the guidance given to children with learning difficulties must be individual and tailored to the needs of each child. An effective guidance program involves collaboration between teachers, counselors, and parents, as well as the use of creative and diverse learning strategies. Some effective strategies found include a multisensory approach, project-based learning, and the use of educational technology. In addition, emotional support and motivation were also found to be key factors in helping children overcome their learning difficulties.This research concludes that structured and ongoing guidance is very important in supporting children with learning difficulties in elementary school. Recommendations for the implementation of guidance programs include training for teachers and counselors, increasing parental involvement, and developing school policies that support inclusion and diversity in teaching methods.